2002
DOI: 10.1007/s10152-001-0091-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variations in the fluxes and composition of seston in near-bottom traps in the southern North Sea

Abstract: In this study we attempted to measure the potential food availability for macrobenthic interface feeders using a new device (sediment recorder) which traps bed load particles at a height of 10 cm above the sea floor. The recorder is positioned flat on the seabed and alternately exposes a shallow collector mounted in a smooth surface mimicking the sediment surface. The samples were analyzed for their content of chlorophyll a (Chl) and dry weight (DM). We compared the sediment recorder data with the results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Witbaard et al (2001) showed that shell growth of Arctica islandica and Chamelea striatula living in the fine sediments of the southern North Sea is slower than that of specimens from coarse sediments. Field measurements have demonstrated that regular resuspension of the fine sediment at the Frisian Front dilutes food concentrations and lowers food quality for suspension feeders (Duineveld & Boon 2002). This may explain the depressed growth rates in fine-grained sediments, as is the case in other areas with frequent resuspension (Emerson 1990, Turner & Miller 1991, Bock & Miller 1994, Urrutia et al 1996, Grant et al 1997, Cranford et al 1998, Gremare et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Witbaard et al (2001) showed that shell growth of Arctica islandica and Chamelea striatula living in the fine sediments of the southern North Sea is slower than that of specimens from coarse sediments. Field measurements have demonstrated that regular resuspension of the fine sediment at the Frisian Front dilutes food concentrations and lowers food quality for suspension feeders (Duineveld & Boon 2002). This may explain the depressed growth rates in fine-grained sediments, as is the case in other areas with frequent resuspension (Emerson 1990, Turner & Miller 1991, Bock & Miller 1994, Urrutia et al 1996, Grant et al 1997, Cranford et al 1998, Gremare et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of benthic food supply at offshore turbulent sites requires scarce resources, i.e. ship time and special instruments (Duineveld and Boon 2002). Growth records deposited in bivalve shells like M. truncata can offer a simple alternative as the organisms integrate conditions over relevant timescales and, moreover, allow retrospective analyses (Richardson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These sediments are subject to faunal induced mixing with the presence of burrowing organisms such as Callianassa subterranea and Upogebia deltaura (Rowden et al, 1998;Dewicke et al, 2002). Previous research has shown that the area is biologically diverse and relatively high in benthic biomass (Dauwe et al, 1998;Dewicke et al, 2002;Duineveld and Boon, 2002), biological activity (Duineveld et al, 1990;Duineveld et al, 1991), and chlorophyll a (Chl a) influx to the sediments compared with adjacent North Sea habitats. Moreover, areas with these characteristics (muddy sediment/high biomass) are known to be more vulnerable to trawling activity than sandy dynamic habitats (Duplisea et al, 2001; Biogeochemical effects from pulse and beam trawl fisheries al., 2006;Queirós et al, 2006, Allen andClarke, 2007;Sciberras et al, 2016).…”
Section: Study Sitementioning
confidence: 99%